11m-5(2m-1)=3(6-m)+1

Simple and best practice solution for 11m-5(2m-1)=3(6-m)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11m-5(2m-1)=3(6-m)+1 equation:



11m-5(2m-1)=3(6-m)+1
We move all terms to the left:
11m-5(2m-1)-(3(6-m)+1)=0
We add all the numbers together, and all the variables
11m-5(2m-1)-(3(-1m+6)+1)=0
We multiply parentheses
11m-10m-(3(-1m+6)+1)+5=0
We calculate terms in parentheses: -(3(-1m+6)+1), so:
3(-1m+6)+1
We multiply parentheses
-3m+18+1
We add all the numbers together, and all the variables
-3m+19
Back to the equation:
-(-3m+19)
We add all the numbers together, and all the variables
m-(-3m+19)+5=0
We get rid of parentheses
m+3m-19+5=0
We add all the numbers together, and all the variables
4m-14=0
We move all terms containing m to the left, all other terms to the right
4m=14
m=14/4
m=3+1/2

See similar equations:

| -5x-41=6(x+6) | | (c+2)(c+3)=14c | | (c+2)(c-3)=14 | | 24=3n(n-5) | | 4(x¡8)=52 | | 3{x+7}=30 | | x3¡5=8 | | 3(x-5)=5/2(x-6)+x/2 | | 4•(x-3)=28 | | 6(r+5)=-2(r-7) | | 5x-7=-3x+8(x-7) | | M*2-7m-144=0 | | 3*(2x-1)-2*(x+3)=2*(2x-1)+(x+3) | | 8x=3x+13 | | 4(3n+2)=6(5n+7)+6 | | 5*(x-4)-3*(2x+4)=x-10 | | x/10+3/10=10 | | 6=3y=-15 | | |3a+4|=|4a-8| | | 6x+3=6(x+9) | | 4-3x/2-7=1 | | -t=-6−3t | | x+2)(x+3)(x-7)(x-8)=144 | | 3/14n=6/5 | | .06x=136.46 | | 2x^2+3=103 | | 2x+20=4x+80 | | 4x+3=2÷ | | 2x-15=3(x+3) | | 90-3x=6x+12 | | 5x+8+9x-7= | | 4/9=x/2 |

Equations solver categories